The Effects of Pre-Sleep Learning on Sleep Continuity, Stability, and Organization in Elderly Individuals - Conte, Francesca; Carobbi, Giulia; Errico, Bruna M.; Ficca, Gianluca (Frontiers in Neurology, 2012)
Several studies have consistently shown that pre-sleep learning is associated to changes of sleep structure. Whereas previous research has mainly focused on sleep states, namely REM and NREM amount, very little attention has been paid to the hypothesis that pre-sleep learning might improve sleep continuity, stability and cyclic organization, which are often impaired in aging. Thus, aim of this research was to assess, in a sample of 18 healthy elderly subjects, whether a memory task administered at bedtime would determine changes in any sleep parameter, with special regard to sleep continuity, stability and organization. To this purpose, a baseline sleep (BL), i.e. a normal sleep with 9-hours Time in Bed (TIB), was compared to a Post-Training sleep (TR), with the same TIB but preceded by an intensive training session. For the latter, a verbal declarative task was used, consisting in learning paired-word lists, rehearsed and recalled for three times in a row. To control for individual learning abilities, subjects were administered several sets of lists with increasing difficulty, until they reached an error rate ≥20 % at third recall. Relative to BL, TR shows a significant reduction in the frequency of brief awakenings, arousals, state transitions, “functional uncertainty” (FU) periods, and in the percentage of time in FU over Total Sleep Time (TST). A significant increase in the number of complete cycles, total cycle time (TCT), and TCT/TST proportion was also found. All these changes are evenly distributed over the sleep episode. No sleep stage measure display significant changes. Scores at retest are negatively correlated with both the frequency of arousals and of state transitions. Our data suggest that pre-sleep learning can yield a beneficial re-organizing effect on elderlies’ sleep quality.The inverse correlation between recall scores and the measures of sleep continuity and stability provides further support to the role of these features in memory processes.